Association of Human Lymphocyte Antigens with Obstructive Airways Disease after Bone Marrow Transplantation - David Spaner; Jeffrey Lipton; Charles K Chan (Canadian Respiratory Journal)
BACKGROUND: Obstructive airways disease (OAD) is a known complication of allogeneic bone marrow transplantation. The etiology of OAD is unknown but is probably multifactorial. The identification of a significant human lymphocyte antigen (HLA) association with the development of OAD might offer some insight into its pathogenesis and serve as a marker to identify prospectively patients at risk for developing OAD.